2005
DOI: 10.1158/0008-5472.can-05-2117
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-7-Dependent Expansion and Persistence of Melanoma-Specific T Cells in Lymphodepleted Mice Lead to Tumor Regression and Editing

Abstract: Active-specific immunotherapy with dendritic cells loaded with peptide derived from the melanoma antigen, gp100, failed to mediate regression of established B16F10 melanoma in normal mice. Dendritic cell vaccination induced activation and subsequent deletion of adoptively transferred naive CD8 + T-cell receptor transgenic (pmel-1) T cells specific for gp100 in normal mice. In lymphodepleted mice, dendritic cell vaccination produced greater T-cell expansion, long-term persistence of memory T cells, and tumor re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 46 publications
1
67
1
1
Order By: Relevance
“…These data, along with the detection of minimal residual disease even in apparently cured mice, led us to investigate whether it would be possible to reactivate the antitumor T-cell activity of the persistently engrafted adoptively transferred T cells. In this respect, it has been shown that the in vivo activity of Pmel T cells can be boosted very effectively, beyond the effects of irradiation alone, by a combination of vaccination and IL-2 Wang et al, 2005). In addition, CPA has often been used as an adjunct to adoptive T-cell transfer due to its multiple, pleiotropic effects (Bracci et al, 2007;Salem et al, 2010;Zhao et al, 2010;Schiavoni et al, 2011), and we have previously reported that low-dose CPA leads to activation of antitumor lymphocytes in vivo (Kottke et al, 2009).…”
Section: ‰ Combination Adoptive Transfer Limits Tumor Escape 1059mentioning
confidence: 99%
“…These data, along with the detection of minimal residual disease even in apparently cured mice, led us to investigate whether it would be possible to reactivate the antitumor T-cell activity of the persistently engrafted adoptively transferred T cells. In this respect, it has been shown that the in vivo activity of Pmel T cells can be boosted very effectively, beyond the effects of irradiation alone, by a combination of vaccination and IL-2 Wang et al, 2005). In addition, CPA has often been used as an adjunct to adoptive T-cell transfer due to its multiple, pleiotropic effects (Bracci et al, 2007;Salem et al, 2010;Zhao et al, 2010;Schiavoni et al, 2011), and we have previously reported that low-dose CPA leads to activation of antitumor lymphocytes in vivo (Kottke et al, 2009).…”
Section: ‰ Combination Adoptive Transfer Limits Tumor Escape 1059mentioning
confidence: 99%
“…There are several hypotheses as to why this happens, including the increased availability of cytokines, which can act as growth factors, and the removal of regulatory cells that would otherwise inhibit engraftment of large numbers. 43,44 The conditioning regimen used in the present study provided a stringent test of the transforming potential of retroviral vectors in T cells, as it enabled long-term persistence of large numbers of transduced T cells, thereby providing ample opportunity for transformation either as a direct result of vector integration, or in combination with other oncogenic events.…”
Section: Absence Of Retroviral Transformation Of T Cells In Micementioning
confidence: 99%
“…[1][2][3][4][5][6] In mice and humans, antigen (Ag) restimulation with vaccination after ACT significantly potentiates the in vivo antitumor efficacy of adoptively transferred self-/tumor-reactive CD8 ϩ T cells. [7][8][9][10][11][12] Efficient translation of this approach to human trials has been limited by a number of technical challenges. For example, tumor-infiltrating lymphocyte (TIL) cultures often have specificity against multiple epitopes rather than a single, defined Ag.…”
Section: Introductionmentioning
confidence: 99%